Data-driven battery state of health estimation based on interval capacity for real-world electric vehicles. (15th October 2022) - Li, Renzheng; Hong, Jichao; Zhang, Huaqin; Chen, Xinbo
Abstract: State of health (SOH) estimation is critical to the safety of battery systems in real-world electric vehicles. Accurate battery health status is difficult to be measured during dynamic and robust vehicular operation conditions. This paper proposes a novel SOH estimation model based on Catboost and interval capacity during the charging process. A year-long operation dataset of an electric taxi is derived with all charging segments separated to construct the research dataset. The charging patterns are analyzed, and the segments with rich aging information are extracted, then a general aging feature of interval capacity is extracted by incremental capacity analysis. Furthermore, comparison with the other six machine learning methods is conducted, and five inputs are determined through Pearson correlation analysis, including start charging state of charge (SOC), end charging SOC, mileage, temperature of probe, and current. The results show the Catboost-based model achieves the best accuracy, with the mean absolute percentage error and root mean squared error limited within 2.74% and 1.12%, respectively. More importantly, a battery aging evaluation strategy and its further research plan is proposed for the application in real-world electric vehicles. Graphical abstract: Image 1 Highlights: A novel SOH estimation mode based on Catboost and interval capacity is presented in detail. Real-world operation data is derived with charging segments separated to construct the dataset. A general aging feature of interval capacity is extracted by incremental capacity analysis. The stability, robustness, and superiority are verified using the actual vehicle operation data. A battery aging evaluation strategy and further research and application plan are proposed.